Key Factors of Marine-Based Tourism Economy in Labuan Bajo, Indonesia - Fauzi, Akhmad; Ismail, Ahyar; Wahyudin, Yudi; Chasanah, Uswatun; Halim, Muhammad Abi Sofian Abdul; Prasetiyo, Didit Eko (Universitas Djuanda, 2025)
Tourism development was a national priority in Indonesia, as outlined in the National Tourism Development Master Plan 2010–2025. Labuan Bajo, designated as one of the “New Bali” destinations, was prioritized for its rich marine biodiversity and high tourism potential. This study examined the key factors that influenced the sustainable development of the region’s marine-based tourism economy. Primary data were collected through Focus Group Discussions (FGDs) using the “World Café” method, involving stakeholders from various sectors. The data were analyzed using the Matrix of Cross Impact Multiplications Applied to a Classification (MICMAC), which mapped the interrelationships among variables. The analysis identified five primary driving factors: participation, infrastructure, regulation, human resource development, and training and education. Governance and conflict were categorized as relay variables, while coordination and information and communication technology were classified as output variables. Welfare, disparity, and income generation were considered autonomous variables. Infrastructure and participation demonstrated a strong indirect influence on income generation. These findings provided strategic insights to guide policymakers and stakeholders in developing integrated and sustainable tourism strategies for Labuan Bajo.